Lifelong training improves anti-inflammatory environment and maintains the number of regulatory T cells in masters athletes - Minuzzi, LG (2018)
PURPOSE: The purpose of this study was to quantify and characterize peripheral blood regulatory T cells (Tregs), as well as the IL-10 plasma concentration, in Masters athletes at rest and after an acute exhaustive exercise test. METHODS: Eighteen Masters athletes (self-reported training: 24.6 ± 1.83 years; 10.27 ± 0.24 months and 5.45 ± 0.42 h/week per each month trained) and an age-matched control group of ten subjects (that never took part in regular physical training) volunteered for this study. All subjects performed an incremental test to exhaustion on a cycle ergometer. Blood samples were obtained before (Pre), 10 min into recovery (Post), and 1 h after the test (1 h). RESULTS: Absolute numbers of Tregs were similar in both groups at rest. Acute exercise induced a significant increase in absolute numbers of Tregs at Post (0.049 ± 0.021 to 0.056 ± 0.024 × 109/L, P = 0.029 for Masters; 0.048 ± 0.017 to 0.058 ± 0.020 × 109/L, P = 0.037 for control) in both groups. Treg mRNA expression for FoxP3, IL-10, and TGF-β in sorted Tregs was similar throughout the trials in both groups. Masters athletes showed a higher percentage of subjects expressing the FoxP3 (100% for Masters vs. 78% for Controls, P = 0.038) and TGF-β (89% for Masters vs. 56% for Controls, P = 0.002) after exercise and a higher plasma IL-10 concentration (15.390 ± 7.032 for Masters vs. 2.411 ± 1.117 for control P = 0.001, ES = 2.57) at all timepoints. KLRG1 expression in Tregs was unchanged. CONCLUSION: Our findings showed that Masters athletes have elevated anti-inflammatory markers and maintain the number of Tregs, and may be an adaptive response to lifelong training.